Supplementation with Lactobacillus helveticus NS8 alleviated behavioral, neural, endocrine, and microbiota abnormalities in an endogenous rat model of depression - Alatan, Husile; Liang, Shan; Shimodaira, Yosuke; Wu, Xiaoli; Hu, Xu; Wang, Tao; Luo, Jia; Iijima, Katsunori; Jin, Feng (Frontiers in Immunology, 2024)
Introductions: Major depressive disorder is a condition involving microbiota-gutbrain axis dysfunction. Increasing research aims to improve depression through gut microbiota regulation, including interventions such as probiotics, prebiotics, and fecal microbiota transplants. However, most research focuses on exogenous depression induced by chronic stress or drugs, with less attention given to endogenous depression. Additionally, research on gut mycobiota in depression is significantly less than that on gut bacteria. Methods: In the present study, Wistar-Kyoto rats were used as an endogenous depression and treatment-resistant depression model, while Wistar rats served as controls. Differences between the two rat strains in behavior, gut bacteria, gut mycobiota, nervous system, endocrine system, immune system, and gut barrier were evaluated. Additionally, the effects of Lactobacillus helveticus NS8 supplementation were investigated. Results: Wistar-Kyoto rats demonstrated increased depressive-like behaviors in the forced swimming test, reduced sucrose preference in the sucrose preference test, and decreased locomotor activity in the open field test. They also exhibited abnormal gut bacteria and mycobiota, characterized by higher bacterial α-diversity but lower fungal α-diversity, along with increased butyrate, L-tyrosine, and L-phenylalanine biosynthesis from bacteria. Furthermore, these rats showed dysfunction in the microbiota-gut-brain axis, evidenced by a hypo-serotonergic system, hyper-noradrenergic system, defective hypothalamic-pituitary-adrenal axis, compromised gut barrier integrity, heightened serum inflammation, and diminished gut immunity. A onemonth L. helveticus NS8 intervention increased the fecal abundance of L. helveticus, reduced the abundance of Bilophila and Debaryomycetaceae, decreased immobility time but increased climbing time in the forced swimming test, reduced hippocampal corticotropin-releasing hormone levels, decreased hypothalamic norepinephrine levels, increased hippocampal glucocorticoid receptor, brain-derived neurotrophic factor, dopamine, and 5-hydroxyindoleacetic acid content, and improved the gut microbiota, serotonergic, and noradrenergic system.The depressive phenotype of Wistar-Kyoto rats is not only attributed to their genetic context but also closely related to their gut microbiota. Abnormal gut microbiota and a dysfunctional microbiota-gut-brain axis play important roles in endogenous depression, just as they do in exogenous depression. Supplementing with probiotics such as L. helveticus NS8 is likely a promising approach to improve endogenous depression and treatment resistant depression.